Agroecological practices for climate change adaptation in semiarid and subhumid Africa - (:unkn) unknown (My University, 2019)
Climate change is expected to strongly affect African farming systems. As vast proportions of African countries’ populations rely on agriculture for livelihood and food security, there is a need to adapt current practices and develop new climate-resilient strategies and farming systems. Here, we inventory and review which agroecological practices currently implemented in semiarid and subhumid Africa can promote adaptation to climate change. This work was carried out through extensive literature research, plus interviews with 24 experts from different African and French NGOs active in agricultural development programs in Africa. We found that: (1) some inventoried practices may not specifically be implemented in response to climate change impacts, yet they aid in adapting to reduced or more variable rainfall and increased temperature, and/or enhance carbon sequestration; (2) other practices promote indirect adaptation by increasing resilience of cropping or livestock systems; (3) many farmers use combinations of different practices to increase overall farming system resilience and through this strategy can achieve efficient adaptation to climate changes, as single practices normally are not sufficient. Our review and evaluation show that a broad variety of agroecological practices provides high potential to adapt to climate change effects in semiarid and subhumid African farming systems.
Keywords: African Research